Effects of an eight-week lumbar stabilization exercise programme on selected variables of patients with chronic low back pain (Bangladesh Journal of Medical Science, 2020)
Background: Lumbar stabilisation exercise has been shown to reduce pain and disability in patients with low back pain but information on its potential benefits in term of back muscle endurance is scarce.Objective: This study was aimed at investigating the effects of augmenting conventional physiotherapy with lumbar stabilization exercises on selected variables of patients with non-specific chronic low back pain (NSCLBP).Methods: Forty individuals with NSCLBP aged 20-60 years were assigned to one of experimental or control groups (20 in each). The experimental group had lumbar stabilisation exercises in addition to conventional therapy (transcutaneous electrical nerve stimulator and infrared) which was the only treatment for the control group. Both groups were treated thrice weekly. Participants’ pain intensity, disability index, kinesiophobia level and back muscle endurance were evaluated at baseline and after 8 weeks.Results: There was significant reduction in pain intensity (experimental: 6.74±1.37; 3.48±1.09; control: 6.57±1.40; 2.96±1.13) and disability index (experimental: 46.60±16.67; 26.55±14.78; control: 32.10±16.16; 24.60±15.27) and increase in back muscle endurance (experimental: 11.05±8.39; 14.30±19.24s; control: 10.85±9.79; 13.90±11.63s) for both groups. Experimental group had significantly greater reduction (p < 0.05) in disability index than the controls (p = 0.048).Conclusion: Augmenting conventional physiotherapy with lumbar stabilisation exercises achieved better reduction in disability than conventional therapy alone in patients with NSCLBP.Bangladesh Journal of Medical Science Vol.19(3) 2020 p.467-474